2009
DOI: 10.1200/jco.2009.21.9584
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Cohort Study of Risk Factors in Cancer Patients of Bisphosphonate-Related Osteonecrosis of the Jaw

Abstract: The conclusions of this study validated dental extractions and use of dentures as risk factors for ONJ development. Ibandronate and pamidronate at the dosages and frequency used in this study seem to exhibit a safer drug profile concerning ONJ complication; however, randomized controlled trials are needed to validate these results. Before initiation of a bisphosphonate, patients should have a comprehensive dental examination. Patients with a challenging dental situation should have dental care attended to befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
303
5
12

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 401 publications
(332 citation statements)
references
References 21 publications
12
303
5
12
Order By: Relevance
“…[1][2][3] Since 2003, more than 1000 cases of bisphosphonate-associated osteonecrosis of the jaw have been documented in the literature, [1][2][3][4][5][6][7][8][9][10][11][12] and more than 3500 cases have been reported to the Food and Drug Administration in the US alone. 4,5 Reported prevalence ranges substantially from 0.01% to 28%, [1][2][3][4][5][6][7][8][9] and high variability persists after correction for type/potency of bisphosphonates and underlying diseases (high-potency intravenous in cancer patients vs. low-potency oral bisphosphonates in osteoporosis patients). [1][2][3][4][5][6][7][8][9] This is more likely to reflect inconsistency and flaws in the collection of data rather than real variations in the prevalence among populations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Since 2003, more than 1000 cases of bisphosphonate-associated osteonecrosis of the jaw have been documented in the literature, [1][2][3][4][5][6][7][8][9][10][11][12] and more than 3500 cases have been reported to the Food and Drug Administration in the US alone. 4,5 Reported prevalence ranges substantially from 0.01% to 28%, [1][2][3][4][5][6][7][8][9] and high variability persists after correction for type/potency of bisphosphonates and underlying diseases (high-potency intravenous in cancer patients vs. low-potency oral bisphosphonates in osteoporosis patients). [1][2][3][4][5][6][7][8][9] This is more likely to reflect inconsistency and flaws in the collection of data rather than real variations in the prevalence among populations.…”
mentioning
confidence: 99%
“…4,5 Reported prevalence ranges substantially from 0.01% to 28%, [1][2][3][4][5][6][7][8][9] and high variability persists after correction for type/potency of bisphosphonates and underlying diseases (high-potency intravenous in cancer patients vs. low-potency oral bisphosphonates in osteoporosis patients). [1][2][3][4][5][6][7][8][9] This is more likely to reflect inconsistency and flaws in the collection of data rather than real variations in the prevalence among populations. 7 The lack of specific diagnostic criteria and a unanimously accepted definition of bisphosphonate-associated osteonecrosis of the jaw is possibly the major cause of this epidemiological inconsistency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that the authors managed through a well-conducted meta-analysis to detect this outcome in a population with a very low incidence rate. In a recently published prospective epidemiological study from Northern Greece, in which ONJ is the primary outcome, the incidence of ONJ is reported to be elevated in those patients receiving zolendronate when compared to patients receiving pamidronate and especially ibandronate [5]. The authors concluded that future RCTs should verify this outcome [5], and the meta-analysis by Mauri et al supports this argument.…”
mentioning
confidence: 96%
“…Reading [4], increasing bisphosphonate accumulation in the skeleton with time may lead to ONJ development. Incidentally, the majority of ONJ cases are reported to occur after administration of over six bisphosphonate doses [5].…”
mentioning
confidence: 99%